Desipramine enhances the stability of atherosclerotic plaque in rabbits monitored with molecular imaging - Zhao, Min; You, Baiyang; Wang, Xiaole; Huang, Jin; Zhou, Ming; Shi, Ruizheng; Zhang, Guogang (PloS one, 2023)
Acid sphingomyelinase (ASM) promotes atherogenesis and acute cardiovascular events. We previously demonstrated ASM inhibitor desipramine attenuated oxidized-LDL-induced macrophage apoptosis in vitro. Here, we aim to determine whether ASM-mediated apoptosis in plaque improves stability in vivo. In this study, rabbits with abdominal aorta balloon injury and a 12-week high-cholesterol diet (HCD) were used to simulate an atherosclerotic plaque model. Atherosclerotic rabbits received oral administration of saline (Control group), atorvastatin (Ator group), or desipramine (DES group). ASM activity and ceramide level were measured by ultra-performance liquid chromatography (UPLC). Plaque morphology was assessed by histochemistry and immunohistochemistry. Apoptosis was evaluated by SPECT/CT imaging of 99mTc-duramycin uptake and TUNEL. We found that increasing ASM activity and ceramide level in atherosclerotic rabbits was abated by additional atorvastatin and desipramine treatment. Meanwhile, the DES and Ator groups were similar in plaque stability, with smaller plaque size, areas of macrophages, higher smooth muscle cell content, and decreased apoptosis and matrix metalloproteinase (MMP) activities relative to the Control group. 99mTc-duramycin uptake of rabbit aorta was significantly higher in Control than in the Normal group, while it was reduced by desipramine and atorvastatin administration. Moreover, the uptake of 99mTc-duramycin positively correlated with apoptotic cell number, macrophage infiltration, and plaque instability. The present study demonstrated that desipramine exerted plaque-stabilizing effects partially by suppressing apoptosis and MMP activity in a rabbit model. And 99 mTc-duramycin SPECT/CT imaging allowed noninvasively monitoring of atherosclerotic disease and evaluation of anti-atherosclerotic therapy.